THE USES OF RESERVES ON THE RIGHT-HAND SIDE OF THE BALANCE SHEET. - Smith, Helen M. (The Accounting Review, 1960)
The word "reserve" has been used to describe a diversified grouping of accounts on the right-hand side of the balance sheet. The various uses and capacities in which the word serves, as well as the many different methods of its creation, have caused perplexity for a long period of time. The ambiguity of the term prompted the Committee on Accounting Procedure of the American Institute of Certified Public Accountants in 1953 to recommend to its members that only certain types of liabilities, known and unknown, be designated as reserves. The Committee on Terminology of the Institute corroborated in the limited use of the term "reserve" with the recommendation that amounts for betterments or plant extensions and for excess cost of replacement of property be included. The conditions surrounding the actual definitive processes make it difficult to draw the line between true reserves and "so-called" reserves although the Institute recommendations to accountants make clear and definite distinctions.